House Republican Decision Making Following the Capitol Riot. Issue 3 (22nd July 2022) - Strawbridge, Michael G.; Lau, Richard R.
ABSTRACT: Former President Donald Trump's unsubstantiated vote-fraud claims following the 2020 presidential election divided the Republican Party. Numerous Republicans supported Trump's efforts to overturn the election, others did not. These futile attempts reached a flashpoint during the January 6 attack on the United States Capitol. Even in the wake of such violence, many House Republicans continued to amplify Trump's baseless claims by voting to exclude the election results from Arizona and Pennsylvania. This article analyzes these roll-call votes to determine the likely motivations for why some House Republicans were still willing to support Trump's position following the Capitol riot. We then replicate our analysis with the January 13 impeachment and the May 19 vote to establish a bipartisan National Commission to Investigate the January 6 Attack on the United States Capitol Complex (January 6 Commission) to investigate the insurrection. Our findings indicate the relevance of constituent preferences, Trump's popularity, legislator ideology, and the racial diversity of constituents represented by Republicans.